Multifixation campimetry on line: a perimeter for the detection of visual field loss using the internet. Issue 10 (23rd September 2003) - Damato, B; Groenewald, C
Abstract : More widespread perimetry would improve opportunities for preventing visual handicap from ocular and intracranial diseases, some of which are life threatening. With internet access becoming more ubiquitous, the authors have developed multifixation campimetry on line, for qualified practitioners and lay individuals around the world, free of charge.